Controlling the Head of the School Administration Section in Managing archives at SMP N 24 Padang - Witri Asri, Rafiqa; Ulmadevi, Ulmadevi; Zahratul Jannah, Nadyya; Yunita, Irma; Arif, M. (GIC Proceeding, 2023)
This research was motivated because researchers found several problems related to the management of archives that are still not running properly. Problems related to archive management that are still not running as a whole. Overall. The role of the head of the Administration section in developing controlling archive management has actually been carried out, but there are still things that need to be improved and addressed again. Need to be improved and addressed again. Given that there are still employees Administration employees who still lack knowledge in archive management. Besides In addition, the role of the head of the Administration section must also be able to coordinate the Administration staff so that they carry out the stages of archive management in accordance with the stages of archive management. Administration staff so that they carry out the stages of archive management in accordance with the existing stages. stages that already exist. The purpose of this research was conducted to find out the stages and obstacles in controlling archive management at SMP N 24 Padang. This research uses descriptive qualitative methods. The results of this study indicate that the stages of archive management at SMP N 24 Padang have five stages in archive management. Padang has five stages in archive management. The stages are: a) Creation and Acceptance Stages, b) Distribution Stages, c) User Stages, d) Maintenance Stages, e) Destruction Stages. User, d) Maintenance Stages, e) Destruction Stages. Then the process of controlling the head of the Administration section in archive management has controlling such as: starting with the Standard Setting Stage, Determining Stage Measurement of Activity Implementation / Measurement of Implementation, Stage of Taking Action. The obstacles faced by the head of the Administration section in controlling archive management at SMP N 24 Padang, first, there are administrative staff who do not finish managing an archive. second, there are still Administration staff who do not understand how to manage archives correctly. do not understand how to properly manage archives.